The Hybridization of Vocational Training and Higher Education in Austria, Germany, and Switzerland - Lukas Graf (Budrich UniPress, 2013)
Austria, Germany, and Switzerland are increasingly relying on hybridization at the nexus of vocational training and higher education to increase permeability and reform their highly praised systems of collective skill formation. This historical and organizational institutionalist study compares these countries to trace the evolution of their skill regimes from the 1960s to today's era of Europeanization, focusing especially on the impact of the Bologna and Copenhagen processes.
Additional information: Zugl.: Dissertation, Freie Universität Berlin, 2012
Keywords: 300; Austria; Germany; Switzerland; Europeanization; Bologna process; Copenhagen process; European Qualification Framework; education; higher education; vocational education and training; social inequality; permeability; institutional change; institutionalism; hybridization